The impact of self-regulatory strategy use on self-efficacy beliefs and motivated learning behavior in study abroad contexts: The case of university students in Italy, Poland and Turkey. (April 2022) - Pawlak, Mirosław; Csizér, Kata
Abstract: The crucial role of individual difference (ID) variables in second language acquisition has long been attested to. It has also been acknowledged that ID factors need to be explored in a contextual manner as their role and impact might vary across learning environments. This is also true about study abroad (SA) where constellations of ID variables determine linguistic and non-linguistic benefits. With this in mind, the study investigated the ways in which self-regulatory strategy use before, during and after the SA might impact self-efficacy beliefs and motivated learning behavior in three contexts: Italy ( N  = 234), Poland ( N  = 86) and Turkey ( N  = 85). A questionnaire was used to collect data in the three countries. One-way and repeated-measures ANOVAs as well as regression analyses showed that even though some tendencies, such as the key role of teacher-initiated strategies during SA, were common across the three contexts, important differences were also uncovered in terms the overall role of self-regulation and the impact of student-initiated strategies. These results provide context-sensitive implications in Europe.